Biomarkers in pediatric heart disease. (August 2014) - Nawaytou, Hythem; Bernstein, Harold S
A biomarker is a characteristic that can be used as an indicator of a biological state. A biomarker can be a clinical observation, laboratory test or an imaging parameter. In this review, we discuss the use of biomarkers in differentiating cardiac from noncardiac disease; predicting the prognosis of patients with heart failure, pulmonary hypertension and dilated cardiomyopathy; diagnosing subclinical cardiac involvement in muscular dystrophy and postchemotherapy cancer patients; detecting acute rejection following heart transplantation; diagnosing Kawasaki disease; aiding the management of postoperative cardiac patients; and managing both common (tetralogy of Fallot) and complex (single-ventricle physiology) congenital heart diseases.